h.hofstede (h.hofstede@hogeland.nl)

       
1. a. 3 (x + 4 + y)
= 3x + 3 4 + 3y
=
3x + 12 + 3y
 
       
  b. 5 (a + 2 + a)
= 5a + 5 2 + 5a
= 10a + 10
 
       
  c. x (2 + y)
= x 2 + xy
= 2x + xy
       
  d. 5 (p + 4 + q)
= 5p + 5 4 + 5q
= 5p + 20 + 5q
 
       
  e. 2 (5 + b + 3 + b)
= 2 5 + 2b + 2 3 + 2b
= 10 + 2b + 6 + 2b
= 16 + 4b
 
       
  f. p (a + 2 + b)
= pa + p 2 + pb
= pa + 2p + pb
       
2. a. 2a(3 + 3b)
= 2a 3 + 2a 3b
= 6a + 6ab
 
       
  b. 5 + 2(6x - 4)
= 5 + 2 6x + 2 -4
= 5 + 12x - 8
= -3 + 12x
 
       
  c. 3x - 4(2 + x)
= 3x - 4 2 - 4 x
= 3x - 8 - 4x
= -x - 8
 
       
  d. -6(3x + 4y)
= -6 3x - 6  4y
= -18x - 24y
 
       
  e. -2(4a - 5b)
= -2 4a - 2 -5b
= -8a - - 10b
= -8a + 10b
 
       
  f. 4 - (3y - 6)
= 4 - 1 (3y - 6)
= 4 - 1 3y - 1 -6
= 4 - 3y + 6
= 10 - 3y
 
       
  g. 6p - 2p (-3 + q)
= 6p - 2p -3  - 2p q
= 6p + 6p - 2pq
= 12p - 2pq
 
       
  h. 2(2a + 3b) - 3(a - 4b)
= 2 2a + 2 3b - 3 a - 3 -4b
= 4a + 6b - 3a + 12b
= a + 18
 
       
  i. 12n - 3n(4 - m)
= 12n - 3n 4 - 3n -m
= 12n - 12n + 3nm
=
3nm
 
       
  j. 13 - 2(-3x - 4y)
= 13 - 2 -3x - 2 -4y
= 13 + 6x + 8y
 
       
  k. -2(a - 2b) - 5b
= -
2a - 2 -2b - 5b
= -2a + 4b - 5b
= -2a - b
 
       
  l. -x(-3 - 4y) + 3x(2 + 6x)
= -x -3  - x -4y  + 3x 2 + 3x 6x
= 3x + 4xy + 6x + 18x2
= 9x + 4xy + 18x2
 
       
3. a. 5 - 2(x + 3) = -5x + 6
5 - 2x - 6 = -5x + 6
-1  - 2x = -5x + 6
-2x = -5x + 7
3x = 7
x = 7/3
 
       
  b. 2(3x + 5) = 8 - 4x
6x + 10 = 8 - 4x
6x = -2 - 4x
10x = -2
x
= -2/10 = -1/5
 
       
  c. 6(4 - 3x) = 2(5x + 8)
24 - 18x = 10x + 16
-18x = 10x - 8
-28x = -8
x = 8/28 = 2/7
 
       
  d. 7 + 7x = -7(-5 - 3x)
7 + 7x = 35 + 21x
7x = 28 + 21x
-14x = 28
x = -2
 
       
  e. 5 - (x - 5) = 6x + 12
5 - x + 5 = 6x + 12
10 - x = 6x + 12
-x = 6x + 2
-7x = 2
x = -2/7
 
       
  f. -4( 5 - 3x) = 12 - 2(4 - 2x)
-20 + 12x = 12 - 8 + 4x
-20 + 12x = 4 + 4x
12x = 24 + 4x
8x = 24
x = 3
 
       

h.hofstede (h.hofstede@hogeland.nl)